2016
DOI: 10.1523/jneurosci.2528-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Dendritic Development and Memory inSorbs2Knock-Out Mice

Abstract: Intellectual disability is a common neurodevelopmental disorder characterized by impaired intellectual and adaptive functioning. Both environmental insults and genetic defects contribute to the etiology of intellectual disability. Copy number variations of SORBS2 have been linked to intellectual disability. However, the neurobiological function of SORBS2 in the brain is unknown. The SORBS2 gene encodes ArgBP2 (Arg/c-Abl kinase binding protein 2) protein in non-neuronal tissues and is alternatively spliced in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 66 publications
3
56
1
Order By: Relevance
“…While our manuscript was under revision, a study on the genetic ablation of Sorbs2 (nArgBP2) in mice was published that showed the reduction of dendritic complexity and excitatory synaptic transmission (22). Unlike our data, Sorbs2 knockout mice did not show significant alterations in dendritic spines.…”
Section: Methodscontrasting
confidence: 78%
See 2 more Smart Citations
“…While our manuscript was under revision, a study on the genetic ablation of Sorbs2 (nArgBP2) in mice was published that showed the reduction of dendritic complexity and excitatory synaptic transmission (22). Unlike our data, Sorbs2 knockout mice did not show significant alterations in dendritic spines.…”
Section: Methodscontrasting
confidence: 78%
“…nArgBP2 knockout mice show manic/bipolar-like behavior resembling many aspects of BD (22,23). The prefrontal cortex, striatum, and amygdala have been implicated in the pathogenesis of the disease (21,36), all of which are brain regions that express nArgBP2 highly (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we examined whether Shank3 deletion differentially affected spine density in D1 MSNs versus D2 MSNs. We applied a modified viral-based method to sparsely label striatal neurons using a membrane-targeted EGFP (EGFPf) delivered with an AAV viral vector (AAV-hSyn1-EGFPf-WPRE-hGH), which could pass the blood-brain barrier to infect neurons when injected into the retroorbital venous sinus (77). We injected AAV-hSyn1-EGFPf-WPRE-hGH into 2-to 4-month-old Shank3B-KO/Drd1a-tdTomato and WT/Drd1a-tdTomato mice and imaged MSNs (Supplemental Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Third, expression of SORBS2 protein was found to be significantly increased in the sera of patients with acute myocardial infarction, but depleted in the infarcted myocardia 24 . However, in vivo cardiac phenotypes have not been reported in a Sorbs2 knock-out (KO) mouse model 25 .…”
Section: Introductionmentioning
confidence: 99%